2010
DOI: 10.1093/mutage/geq064
|View full text |Cite
|
Sign up to set email alerts
|

Micronuclei in neonates and children: effects of environmental, genetic, demographic and disease variables

Abstract: Children may be more susceptible to the effects of the environmental exposure and medical treatments than adults; however, limited information is available about the differences in genotoxic effects in children by age, sex and health status. Micronucleus (MN) assay is a well established method of monitoring genotoxicity, and this approach is thoroughly validated for adult lymphocytes by the Human Micronucleus Biomonitoring project (HUMN.org). Similar international undertaking is in progress for exfoliated bucc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 51 publications
4
36
1
2
Order By: Relevance
“…Micronuclei formation in peripheral blood T-lymphocytes may be regarded as a phenotypic endpoint that reflects the deleterious effects on chromosomes because of the (combined) exposure to genotoxic carcinogens (51). Previous studies report that the baseline MN frequency is relatively low in newborns and no differences in gender have been identified (29,52), which is confirmed in our study.…”
Section: Micronuclei Frequenciessupporting
confidence: 89%
“…Micronuclei formation in peripheral blood T-lymphocytes may be regarded as a phenotypic endpoint that reflects the deleterious effects on chromosomes because of the (combined) exposure to genotoxic carcinogens (51). Previous studies report that the baseline MN frequency is relatively low in newborns and no differences in gender have been identified (29,52), which is confirmed in our study.…”
Section: Micronuclei Frequenciessupporting
confidence: 89%
“…In addition, these groups did not differ statistically in the MN frequencies in differentiated cells (data not shown). Bloching et al (2007) and Holland et al (2011) found a relationship between age and increased MN frequencies. These observations could be explained by cellular senescence, since the increase of MN frequencies with age occurs probably due to a combination of effects that include mutations accumulation acquired in genes involved in DNA repair, segregation of chromosomes, checkpoints cycle mobile, numerical and structural aberrations in chromosomes caused by exposure to endogenous and exogenous genotoxins (FENECH; BONASSI, 2011).…”
Section: Resultsmentioning
confidence: 95%
“…Children whose parents or relatives were smokers, consumed coffee or tea in excess, used chronic medications, have been exposed to X-rays in the past 6 months, have been exposed to contaminants in drinking water or to any other environmental pollutants close to their place of residence 28 were excluded because all these factors are considered potentially confounding for results.…”
Section: Populationmentioning
confidence: 99%